Two new species of Asymphyloptera Collin (Diptera: Empididae: Clinocerinae) from Colombia, with an updated key to males of New World species - Ramos-Pastrana, Yardany; Córdoba-Suarez, Eric; Sinclair, Bradley J. (Zootaxa, 2023)
The genus Asymphyloptera is recorded from Colombia for the first time, with the description of two new species from Parque Natural Regional Cerro Páramo de Miraflores: A. miraflorensis sp. nov. and A. tama sp. nov. The two species are illustrated, and an updated key and distribution map for all New World species are presented.